If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(6 + x) = 4(x + -2) (6 * 5 + x * 5) = 4(x + -2) (30 + 5x) = 4(x + -2) Reorder the terms: 30 + 5x = 4(-2 + x) 30 + 5x = (-2 * 4 + x * 4) 30 + 5x = (-8 + 4x) Solving 30 + 5x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 30 + 5x + -4x = -8 + 4x + -4x Combine like terms: 5x + -4x = 1x 30 + 1x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 30 + 1x = -8 + 0 30 + 1x = -8 Add '-30' to each side of the equation. 30 + -30 + 1x = -8 + -30 Combine like terms: 30 + -30 = 0 0 + 1x = -8 + -30 1x = -8 + -30 Combine like terms: -8 + -30 = -38 1x = -38 Divide each side by '1'. x = -38 Simplifying x = -38
| 4x+7=-6+47 | | 2(4x+2)=7(x+6) | | 6x^6/2x^2y | | N-12=3x | | 5(3x+5)=4(3x+4)+3x | | 2(x+1)=7-5(2x+1) | | N-12=5x | | 2y+0x=4 | | 10s^2-s-s^2-16-3s+11= | | X^2+52x+100= | | 6(6v+6-5)=1+6r | | 2x-8=5x+(10) | | -12=5k-8 | | 4b-2b=20 | | x^2-30y+352=0 | | 4x+52=4(2x+8) | | 8y+7y=-75 | | (5x+1)(2x)= | | 2x+3=7x+(-42) | | 5x^4-12x^2+3=0 | | 3k=5k+7 | | -11+3x=x-15 | | 4.905x^2-4x-22=0 | | 2x^2-1528x+2821=0 | | 5p+14=29 | | m/4=2 | | 8r^2-6r-9=0 | | 9x-4=5x+32 | | 2-4x=12+x | | 5x-7=-4x+-25 | | 6(x+2)=60-6x | | 3-10=2+32 |